Treatment results in patients with acute limb ischemia - V. A. Gubka; I. A. Konovalenko; O. V. Suzdalenko (Patologìâ)
Aim. Acute limb ischemia (ALI) is one of the most serious subjects for life quality declining and often results in patients’ disability. The incidence of ALI increases from year to year and currently counts about 50 to 100 cases per 100 000 persons in EU and USA.